The Underlying Database of an Instrument for Economic and Social Policy Analysis for the Azores. Application and Extension to 2005 - Santos, Susana (2017)
In this paper a conceptual reflection is carried out and a practical and methodological guide is provided to the work undertaken with the aim of updating for 2005 a Social Accounting Matrix (SAM) constructed for 2001 as a database for a Computable General Equilibrium (CGE) model for the Azores. The construction of a similar SAM to support an application of the same model for Portugal is also part of that same work. A top-down approach is adopted, and the study adheres to the principle that databases for national and regional models (namely SAMs) should be consistent with national and regional accounts.